Cancer-associated fibroblast related gene signature in Helicobacter pylori-based subtypes of gastric carcinoma for prognosis and tumor microenvironment estimation in silico analysis - Xu, Ruofan; Yang, Le; Zhang, Zhewen; Liao, Yuxuan; Yu, Yao; Zhou, Dawei; Li, Jiahao; Guan, Haoyu; Xiao, Wei (Frontiers in Medicine, 2023)
Gastric cancer (GC) remains the major constituent of cancer-related deaths and a global public health challenge with a high incidence rate. Helicobacter pylori (HP) plays an essential role in promoting the occurrence and progression of GC. In this study, 52 HP-related genes (HRGs) were screened based on the GSE84437 and TCGA-GC databases. A total of 804 GC samples were analyzed respectively and clustered into two HP-related subtypes. The differential expression genes (DEGs) identified from the two subtypes were proved to have a relation with TME. Weighted correlation network analysis (WGCNA) was performed to verify the correlation between the DEGs and cancer-associated fibroblasts which were key components in the tumor microenvironment. The least absolute shrinkage and selection operator (LASSO) was executed to screen out 21 gene signatures that were regarded as cancer-associated fibroblast-related differential expression genes (CDEGs). Then, a CDEGs-Score was constructed and its prediction efficiency in GC patients was conducted for validation. Overall, a highly precise nomogram was established for enhancing the adaptability of the CDEGs-Score. Furthermore, our findings revealed the applicability of CDEGs-Score in the sensitivity of chemotherapeutic drugs. In general, our research provided bran-new possibilities for comprehending HP-related GC, evaluating survival, and more efficient therapeutic strategies.